Perceptions, Opinions, Beliefs, and Attitudes About Physical Activity and Exercise in Urban-Community-Residing Older Adults - Elgloria A. Harrison; Lillie Monroe Lord; Elmira Asongwed; Phronie Jackson; Tiffany Johnson-Largent; Anne Marie Jean Baptiste; B. Michelle Harris; Tia Jeffery (SAGE Publishing, 2020)
Background: This research study illustrates the perceptions, opinions, beliefs, and attitudes of older adults residing in an urban community as major factors to understanding barriers and motivators in older African Americans, Hispanics, and Asians adults within Washington, DC. Methods: Eight focus group sessions conducted with 58 older adults to determine their understanding of physical activity and exercise, as well as of barriers to, motivators for, and benefits of physical activity and exercise. Results: The results showed that dance was the preferred physical activity and exercise, fixed or limited income were the main barriers, and prolonged life, more energy, and a stronger body were the main benefits. Conclusion: The results will assist in recommendations to policy makers on programs for older adults that will increase physical activity and exercise for local citizens. These interventions are more likely to increase older adults' ability to remain in their communities and improve their overall health and well-being.